A Qualitative Exploratory Study of the Factors Causing Academic Stress in Undergraduate Students in Pakistan - Muhammad Saeed (IDEA PUBLISHERS, 2020)
Academic stress is becoming an alarming mental health problem in Pakistan. The study aims to explore the causes of academic stress in the undergraduate students in Khyber Pakhtunkhwa, Pakistan. Qualitative exploratory research design is adopted for this study. Data is elicited through structured-interview guide from 80 students from different study programs at the University of Malakand. Findings of the study show that nearly all (96.25%) students experienced an academic stress. Further, main causes of academic stress mentioned by students include: the lack of time management (90%); the semester system and frequent exams (86%); high study load and lengthy syllabi (80%); financial constraints (78%); favouritism and discrimination (72%); ineffective teacher-student relationship (68%); conventional and multilingual teaching style (60%); family and parental expectations (56%); and difficulty in adjustment to the university environment (44%). This study concludes that academic stress can be curbed by revamping on the identified factors, establishment of effective counselling services, and other efficient coping strategies.